Nursing care for a patient diagnosed with eating disorders in the form of anorexia - Nawłatyna, Weronika; Myszka, Paulina; Pawłowski, Piotr; Jakubowska, Klaudia Olga; Kościołek, Aneta (Journal of Education, Health and Sport, 2019)
Introduction: Nowadays, the problem of eating disorders is becoming more and more common in the society. It affects not only the youth but also adults. The canons of beauty presented by tabloids or advertisements become a benchmark of value for many people who, in pursuit of a perfect figure, are willing to make many sacrifices even at the expense of their own health and life. It is estimated that about 8 – 9% of the population is affected by eating disorders in the form of anorexia or bulimia. Mortality constitutes about 20% of diagnosed cases. A timely diagnosed disorder can be treated mainly with the help of appropriate therapeutic techniques, which allows symptoms to resolve in a significant number of patients. Aim: The aim of the study is to present the tasks of a nurse in care for a patient with diagnosed eating disorders in the form of anorexia. Methods and materials: The study was based on the individual case study method. The adopted research techniques were as follows: the interview, nursing observation, measurements and the analysis of the patient’s medical record documentation. The following research tools were used for the study: the Individual Nursing Care Card, the NRS for pain assessment, the MNA for nutrition status and the Beck Depression Inventory. Findings: During the research process, eight nursing diagnoses based on the patient’s health issues were made. Conclusions: Nursing problems in the care of a patient diagnosed with eating disorders in the form of anorexia arise from the disease and the accompanying complications.